Preparation and in vitro antibacterial activity against Pantoea stewartii causing jacfruit bronzing disease of nano ZnO/oligochitosan-iodine complex - Bui, Duy Du; Nguyen, Trong Hoanh Phong; Tuan, Le Nghiem Anh; Tran, Phuoc Tho; Nguyen, Quoc Hien (Vietnam Journal of Science and Technology, 2023)
Nano ZnO/chitosan oligosaccharide (ZnO/COS) and nano ZnO/chitosan oligosaccharide-iodine complex (ZnO/COS-I2) prepared in this study are new materials consisting of ZnO nanoparticles (12.3 - 15.0 nm) dispersed in COS and COS-I2 solutions. Both ZnO/COS and ZnO/COS-I2 nanomaterials have the ability to resist Pantoea stewartii (P. stewartii) causes jackfruit bronzing bacterium. The COS with a low molecular weight (Mw) of 3,320 g/mol has the main advantage that is completely soluble in both acidic and alkaline mediums to pH 9. The characterizations of materials nanomaterials were determined by gel permeation chromatography (GPC), nuclear magnetic resonance (1H-NMR), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The results of the in vitro test against P. stewartii of ZnO/COS-I2 nanomaterial showed that the antibacterial efficacy is 100% at 500 ppm of active ingredient concentration. The studied results also confirmed that nano ZnO/COS-I2 nanomaterial has the ability to inhibit bacteria higher than that nano ZnO/COS nanomaterial. Therefore, the ZnO/COS-I2 nanomaterial has great potential to use as an effective agent to control the serious damage jackfruit bronzing bacterium and has no specific treatment.